THE LEGAL ASPECTS AND URGENCY OF LEASE AGREEMENTS MADE BEFORE A NOTARY AND REGISTERED AT THE LAND OFFICE ACCORDING TO ARTICLE 127B OF THE REGULATION OF THE MINISTER OF AGRARIAN AFFAIRS AND SPATIAL PLANNING/NATIONAL LAND AGENCY NUMBER 16 OF 2021 - Syahira Sumantri, Nabila; Purba, Hasim; Suprayitno, Suprayitno (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The lease agreement for land and buildings plays an important role in providing legal certainty and protection for the parties involved. In practice, however, such agreements are often not registered at the Land Office as specified in Article 127 B of the Regulation of the Minister of Agrarian Affairs and Spatial of the National Land Agency Number 16 of 2021. This leads to various legal issues that can affect certainty and legal protection for the parties. Based on this issue, this study formulates three main research questions: (1) What is the urgency of lease registration by the interested parties with the Land Office? (2) How is legal protection provided for tenants who register their lease objects at the Land Office under Article 127 B of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 16 of 2021? (3) What are the possible legal impacts, both disadvantages and advantages, of registering lease agreements with the Land Office as regulated by Article 127 B of the said regulation? This research employs a normative juridical method. This research approach also uses a conceptual approach (Conceptual Approach), the conceptual approach is intended "to analyze legal materials so that the meaning contained in legal terms can be known". Data was obtained through literature studies, reviews of relevant regulations, and legal document analysis. The findings indicate that lease agreements made before a notary provide authentic evidentiary strength, while registration at the Land Office offers legal certainty to third parties. However, challenges remain in implementing this registration, including a lack of public awareness and minimal dissemination of the importance of registration. The conclusion of this study emphasizes that lease agreements made before a notary and registered at the Land Office not only provide stronger legal protection but also enhance transparency in managing land and building assets. The proposed recommendations include increasing legal education for the public the benefits of agreement registration, simplifying registration procedures, and strengthening the role of notaries in ensuring compliance with the relevant regulations.